Polymer-Based Nano-Adsorbent for the Removal of Lead Ions: Kinetics Studies and Optimization by Response Surface Methodology - Abdullahi Haruna Birniwa; Sana Kehili; Mujahid Ali; Haruna Musa; Umar Ali; Shamsul Rahman Mohamed Kutty; Ahmad Hussaini Jagaba; Shehu Sa’ad Abdullahi; Elsayed Mohamed Tag-Eldin; Habibun Nabi Muhammad Ekramul Mahmud (Separations, 2022)
This work successfully created a polypyrrole-polyethyleneimine (PPy-PEI) nano adsorbent for the elimination of the lead ion Pb2+ from an aqueous solution. An efficient conducting polymer-based adsorbent called as was created using ammonium persulfate (NH4)2S2O8 as an oxidant (PPy-PEI). The PEI hyper-branched polymer with terminal amino groups was added to the PPy adsorbent to offer heavy metals more effective chelating sites. Pb2+ removal from aqueous solution using polyethyleneimine micro adsorbent was successfully accomplished using a batch equilibrium technique (PPy-PEI). The generated water-insoluble polymer nanoadsorbent had enough nitrogen atoms; therefore, an effort was made to link PEI, a water-soluble PPy, with PPy, a conjugated polymer, for lead ion adsorption from an aqueous solution. The generated PPy-PEI nanoadsorbents were discovered to have average particle sizes of 18–34 nm and a Brunauer-Emmet-Teller surface area of 17 m2/g, respectively. The thermal behavior of the composites was investigated using thermo gravimetric and differential scanning calorimetric methods. The lead ion adsorption efficacy of pure polypyrrole was found to be 38%; however, a batch equilibrium technique employing nanoadsorbent revealed with the maximum adsorption capacity of 75.60 mg g−1. At pH 10 and 30 min of contact time at 50 °C, 0.2 g of adsorption was shown to be the ideal dosage. X-ray diffraction analysis, energy-dispersive ray spectroscopy, and Fourier transform infrared ray spectrum support the lead ion adsorption by PPy-PEI nanoadsorbents. The cauli-like structure was visible using field emission scanning electron microscopy. Studying the thermodynamic showed that the adsorption was endothermic as illustrated from the positive value of value of ΔH° is 1.439 kJ/mol which indicates that the uptake of Pb2+ onto nanoadsorbent PPy-PEI could be attributed to a physical adsorption process. According to the values of ΔG°, the adsorption process was spontaneous at all selected temperatures. The positive value of ΔS° value (43.52 j/mol) suggested an increase in the randomness at the solid/solution interface during the adsorption process. The adsorption data meet the pseudo-second-order kinetic model and suited the Langumuir isothermal model effectively.